Data from: Morphology of western and semipalmated Sandpipers 1978-2020 - Ydenberg, Ronald; Fernández, Guillermo; Ortiz Lopez, Enver; Lank, David (Zenodo, 2023)
Increasing predation danger can select for safety-enhancing modifications to prey morphology. We document multi-decade wing lengthening of a Pacific flyway migrant, the western sandpiper ( Calidris mauri ), and contrast this with contemporaneous wing shortening of the closely related semipalmated sandpiper ( C. pusilla ) on the Atlantic flyway. We measured > 12,000 southbound western sandpipers captured 1978–2020 at a major stopover site in British Columbia. Wing length increased at 0.074 mm y -1 (SE = 0.017; p < 0.0003) for adults, and 0.087 mm y -1 (SE = 0.029; p < 0.007) for juveniles. These rates are of similarly large magnitude (4–5% overall), but opposite in direction, to the rate we previously reported for semipalmated sandpiper adults (-0.103 mm y -1 ). In both species, the change is specific to wings rather than being part of general body size change. We interpret both trends as responses to the ongoing strong increase of peregrine falcon (Falco peregrinus) populations since the mid-1970s, an important predator encountered by these species in contrasting ways during migration. Western sandpiper and peregrine migrations have temporal and spatial overlap. Longer wings enhance migratory speed and efficiency, enabling western sandpipers to decrease overlap by advancing to safer zones ahead of falcon passage. In contrast, semipalmated sandpipers primarily encounter peregrines as residents at migratory staging sites. Shorter wings improve acceleration and agility, helping migrants to escape attacks. Juvenile western sandpiper wing length also shows a component additive to the lengthening trend, shifting between years at 0.055 mm d -1 with the highly variable snowmelt date, with wings shorter following early springs. On the Pacific flyway, the timing of peregrine southward passage advances with snowmelt, increasing the relative exposure of juveniles to post-migratory resident peregrines. We interpret this annual wing length adjustment as an induced defense, made possible because snowmelt timing is a ...